2010
DOI: 10.1001/jama.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Association Between 9p21 Genomic Markers and Heart Disease

Abstract: REVENTING AND MANAGING CARdiovascular disease (CVD) presents a challenge for health care and public health. 1,2 Nonmodifiable risk factors include increasing age, male sex, and heredity. Modifiable risk factors include smoking, hypertension, dyslipidemia, obesity, physical inactivity, and diabetes. [3][4][5] Among men, the annual rate of initial CVD events increases from 3 to 74 per 1000 from ages 35 to 44 years to ages 85 to 94 years, respectively. Similar increases occur among women a decade later. 6 Biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 70 publications
10
110
2
4
Order By: Relevance
“…There was no evidence showing that Since only one case-control study was identified in Africans, more well-designed genetic studies between rs1333049 and CHD in Africans are required. Compared with the previous meta-analyses of rs1333049 and CHD 23,27,28) , our meta-analysis included more datasets (18 more than Schunkert et al, 8 more than Palomaki et al and 13 more than Guo et al). Furthermore , we also excluded 2 stages that did not meet HWE in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence showing that Since only one case-control study was identified in Africans, more well-designed genetic studies between rs1333049 and CHD in Africans are required. Compared with the previous meta-analyses of rs1333049 and CHD 23,27,28) , our meta-analysis included more datasets (18 more than Schunkert et al, 8 more than Palomaki et al and 13 more than Guo et al). Furthermore , we also excluded 2 stages that did not meet HWE in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the question was then posed as to the relative importance of this one marker in clinical risk prediction. In both a prospective cohort study of white women 49 and a meta-analysis of possible clinical utility, 50 knowledge of the 9p21 genotype added little or nothing to traditional risk factor assessment. The Evaluation of Genomic Applications in Practice and Prevention Working Group recently evaluated 9p21 and 57 other genetic variants linked by GWAS to coronary artery disease and "… found that the magnitude of net health benefit from use of any of these tests alone or in combination is negligible. "…”
mentioning
confidence: 99%
“…1.10-1.15, some publication bias must be expected since only positive results have been published so far. 13,20,[21][22][23] Four studies, with quite different designs, suggested a possible, but weak, association between the rs9818870 polymorphism at the MRAS locus and CVD risk. [8][9][10][11] In comparison with these studies, we failed to detect this polymorphism as a risk for ACS development in the Czech-Slavonic population.…”
Section: Discussionmentioning
confidence: 99%